Prevalence of Helmet Induced Headache among Bikers - Muhammad Ahmad, Aqsa Naveed, Saba Riaz, Aamir Gul Memon, Shahzaib Anwer, M. Hanan Zafar, M. Sanaullah, Saleh Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find prevalence of helmet induced headache among bikers. Methods: A cross sectional study using convenient sampling was conducted on male bike riders of Lahore. After approval from ethical committee participants were selected on the basis of inclusion and exclusion criteria. Informed consent was taken. 102 participants filled out self-made questionnaire. Data was analyzed by using SPSS version 21 in form of frequencies, mean, standard deviation and pie chart. Results: The mean age of participants was 22.77±1.72 years. A total of 52 participants (51%) were reported having headache. Prevalence of helmet induced headache came out to be 6(11.5%) among bikers. A total of 83% used helmet occasionally and 18.17% reported to use it always. The duration of headache for half of the participants (50%) was 20-30 min after wearing helmet, 38.5% had headache duration lasting for 1-5 days in a month. Majority had stabbing (25%) type of pain, among them only (9.6%) visited hospital due to headache. Conclusion: There was high prevalence of headache (stabbing and aching) in bikers but mostly didn’t report complaint of headache specifically while wearing helmet or after removing it. Keywords: Headache, helmet, prevalence, primary prevention